Model-Based Identification of the Base of the Gas Hydrate Stability Zone in Multichannel Reflection Seismic Data, Offshore Costa Rica. (28th December 2009) - Gehrmann, Romina; Müller, Christian; Schikowsky, Peter; Henke, Thomas; Schnabel, Michael; Bönnemann, Christian
Abstract : Along the pacific margin offshore Costa Rica the Bottom Simulating Reflector (BSR) shows a patchy occurrence in 2-D seismic reflection profiles. The reason for this can be either lack of free gas beneath parts of the gas hydrate stability zone (GHSZ) or poor seismic imaging. We compare far to near offset stacked common midpoint sections to reduce imaging ambiguity utilizing the amplitude variation with offset effect and thus successfully distinguish BSRs from regular sediment reflections. In combination with 1-D modeling of the base of the GHSZ we disqualify or qualify reflections in the predicted depth range as BSR. Additionally we calculate the heat flow and compare it with an analytical solution to detect thermal anomalies, for example, at the frontal prism. The higher confidence in BSR depths based on the far offset stacks and heat flow calculations allows further analyses on gas hydrate concentration estimates and tectonic evolution of the margin.